Improving heterogeneous catalysis for biodiesel production process - Onukwuli Dominic Okechukwu; Ezeugo Joseph; Ude Callistus Nonso; Nwosu-Obieogu Kenechi (Cleaner Chemical Engineering, 2022)
The relevance of heterogeneous catalysis in biodiesel production cannot be overemphasized, as heterogeneous catalysts have eliminated the demerits associated with a homogeneous catalysts. Some heterogeneous catalysts experience drawbacks such as partial recoverability and reusability, energy and waste conservation issues during biodiesel processing and leaching of active catalyst sites. This paper highlights and summarizes several heterogeneous catalysts used in biodiesel production. The catalyst preparation, reaction conditions, feedstock, and biodiesel yield for the heterogeneous base and acid catalysts were emphasized. The inability of heterogeneous base catalysts to trans-esterify low-grade oil with high free fatty acid (FFA) is a primary concern; the cost of processing low-grade oil with high FFA using heterogeneous acid catalysts is also a big issue. Nano-doped heterogeneous catalysts with unique properties were recommended because they can process oil with high FFA transesterification, improve reaction efficiency, simplify production, reduce the leaching of active sites, enable better biodiesel yield by minimizing energy and waste, and increase catalyst recoverability, activity, selectivity and durability.